Relationship between Emotional Intelligence, Social Skills, and Anxiety: A Quantitative Systematic Review - Ramos-Galarza, Carlos; Rodríguez-Naranjo, Brayan; Brito-Mora, Deyaneira (Emerging Science Journal, 2024)
Introduction: Emotional intelligence allows us to manage, regulate, and recognize our emotions and those of others, also allowing us to face and solve problems by choosing to provide an appropriate response to the situation experienced by a subject. Social skills are the behaviors that an individual emits in the interpersonal context through their feelings, rights, and opinions, seeking to resolve conflict situations immediately, minimizing the likelihood of experiencing them in the future. Anxiety appears in the individual when he perceives certain situations as threatening or dangerous, hindering his ability to provide an adequate response, being excessive, uncontrollable, or lasting, and this is classified as a mental disorder. Objective: The objective of this study is to describe the relationship between emotional intelligence, social skills, and anxiety. Methods: A quantitative methodology has been employed, basing the study on a systematic review of previous research using the Scopus, Scielo, Redalyc, and Google Scholar repositories. Findings: An initial sample of 1722 articles was obtained, which passed through inclusion and exclusion criteria, resulting in 73 articles. Novelty:The contribution of this study lies in understanding that low anxiety levels lead to better performance of emotional intelligence and social skills. This situation allows people to resolve conflicts that arise in the daily lives of individuals. Doi: 10.28991/ESJ-2024-08-06-025 Full Text: PDF